2020
DOI: 10.1093/infdis/jiaa372
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparity of Coronavirus Disease 2019 in African American Communities

Abstract: The COVID-19 pandemic has unveiled unsettling disparities in the outcome of the disease among African Americans. These disparities are not new, but are rooted in structural inequities that must be addressed to adequately care for communities of color. We describe the historical context of these structural inequities, their impact on the progression of COVID-19 in the African American (Black) community, and suggest a multifaceted approach to addressing these healthcare disparities. Of note, terminology from sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
98
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 6 publications
10
98
1
1
Order By: Relevance
“…Poverty is arguably the most prominent feature of food insecurity. Research specifically among communities of color is of high urgency, as the additional social and structural constraints that lead these families to have an increased risk of food insecurity have also led to these families to be disproportionately impacted by the pandemic [ 116 , 117 ]. Racial discrimination is associated with substantial increases in an individual’s risk of food insecurity [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poverty is arguably the most prominent feature of food insecurity. Research specifically among communities of color is of high urgency, as the additional social and structural constraints that lead these families to have an increased risk of food insecurity have also led to these families to be disproportionately impacted by the pandemic [ 116 , 117 ]. Racial discrimination is associated with substantial increases in an individual’s risk of food insecurity [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous data have shown that people of ethnicity and color have relatively poor access to healthcare services and the provision of treatment (55)(56)(57)(58). During crises like COVID-19, these syndemic factors become important as to how historical health and social disparities along with emerging or current factors, such as epidemics, exacerbate the negative consequences on ethnic or minority groups (58).…”
Section: Impact Of Covid-19 On Ethnic or Minority Groupsmentioning
confidence: 99%
“… 7 COVID-19 ethnic and social disparities have been observed overseas. 8 , 9 New Zealand's response sought to prevent COVID-19 disparities and minimise transit of infection to lower-income Pacific countries. 6…”
Section: Introductionmentioning
confidence: 99%